"I mute my echo when I talk politics": Connecting Smart Home Device Users' Concerns to Privacy Harms Taxonomy. (September 2022) - Chhetri, Chola; Motti, Vivian
With the proliferation of Internet of Things devices, smart home devices are expected to increase in use. However, experts have raised privacy concerns regarding these devices. As the body of literature on understanding privacy concerns continues to emerge, we realize the need for a privacy concerns taxonomy to standardize and facilitate common understanding of privacy concerns. To address this gap, we conducted 25 interviews of smart home device users and analyzed their privacy concerns qualitatively. This paper contributes analysis of user privacy concerns from the angle of privacy taxonomy theory. It examines whether privacy concerns could be characterized by Solove's taxonomy of privacy, which is a well-recognized privacy taxonomy for informational privacy. We further discuss results and their implications.